Evaluation of the Implementation of Good Drug Distribution Methods (CDOB) from the Pharmacy Warehouse of the Health Service to Upt Health Centers in Bengkalis Regency in 2022: Evaluasi Pelaksanaan Cara Distribusi Obat Yang Baik (CDOB) Dari Gudang Farmasi Dinas Kesehatan Ke Upt Puskesmas Kabupaten Bengkalis Tahun 2022 - Rahwana T; Reno Renaldi; Welly Sando; Dami Yanthi (Badnur Medisa Group, 2022)
Distribution is the most important step in meeting the need for medicines that are evenly distributed to all Puskesmas in Bengkalis Regency, Sungai Alam Health Center and Seat Baru, is was found that were vacancies for certain drug item and drug that had expired at the Puskesmas. Dtrug needs planning, which was based on usage complications. Medicines in all puskesmas have not been implemented properly by the Phamarcy Department of Health one of the reasons is the limited distribution of distributors in supplying drugs. The purpose of this study is to determine the evaluation of Grug Distribution from the Pharmaceutical at the pharmacy werehouse to Sungai Alam and Selat Baru Bengkalis Regency in 2022. This type of research is a descriptive evaluation study with a qualitative method. The research subject is the Head of the Pharmaceutical Section, the Head of the Health Center, the person in charge. Research time March-June 2022. Data collection was carried out by in-depth interviews, document search and observations. The Results showed that the implementtation of a good drug distribution method in pharmacy werehouses had not been carried out in accordance with the operational standars. And in the projection of thee need for drug, is it hope that the process of ordering drugs can improve earlier and coordinate more optimally with the Health Office regarding the State revenue Budget Drug Allocation by the Provincial Health logistics pharmacy Installation to Bengkalis regency.